“Can I afford to live today?” The emotional toll of navigating the healthcare system with type 1 diabetes - Harel, Shiraz; Lukasik, James; Wilcox, Annabelle; Lipska, Kasia J.; Weinzimer, Stuart A.; Suttiratana, Sakinah C.; Nally, Laura M. (Frontiers in Endocrinology, 2025)
ObjectivesPeople with diabetes (PWD) face significant barriers to accessing insulin and diabetes supplies, including high prices, leading some to turn to social media for material support. This study explores emotions among PWD who have relied on assistance from social media networks when navigating access to diabetes medications and supplies (DMS).MethodsWe conducted a mixed methods study of individuals with type 1 diabetes (T1D) and their caregivers who have used social media to obtain DMS. Participants were recruited through social media based on self-reported use of social media to obtain diabetes support. Transcripts of semi-structured, telephone interviews were analyzed and categorized, and consensus discussions resolved discrepancies and refined definitions of themes.ResultsThirty individuals (mean age 31+/- 8 years, 29 female, 5 caregivers) were interviewed. The analysis revealed four categories of emotions: anxiety and stress, fear of health problems and financial consequences, frustration with the healthcare system, and feelings of powerlessness and vulnerability. Nearly all interviewees reported anxiety or stress due to the financial burden of managing diabetes and fear for their or their child’s health and safety. Diabetic ketoacidosis, unnecessary bodily harm or sickness, or fear of dying due to running out of insulin worried participants. Most participants described the process of obtaining DMS to be more stressful than their daily diabetes management.ConclusionsPWD described strong negative emotions related to navigating the healthcare system and acquiring DMS. Policy changes are urgently needed to support to individuals with type 1 diabetes in order to enhance their quality of life, guarantee equitable access to care, and cultivate a more compassionate and inclusive healthcare system. The reported magnitude of stress is notable, especially given the attention typically focused on the stress of diabetes management.